Abnormal development of sensory-motor, visual temporal and parahippocampal cortex in children with learning disabilities and borderline intellectual functioning - Baglio, Francesca; Cabinio, Monia; Ricci, Cristian; Baglio, Gisella; Lipari, Susanna; Griffanti, Ludovica; Preti, Maria G.; Nemni, Raffaello; Clerici, Mario; Zanette, Michela; Blasi, Valeria (Frontiers in Human Neuroscience, 2014)
Borderline intellectual functioning (BIF) is a condition characterized by an intelligence quotient (IQ) between 70 and 85. BIF children present with cognitive, motor, social and adaptive limitations that result in learning disabilities and are more likely to develop psychiatric disorders later in life. Aim of this study was to investigate brain morphometry and its relation to IQ level in borderline intellectual functioning children. Thirteen children with BIF and 14 age- and sex-matched typically developing children were enrolled. All children underwent a full IQ assessment (WISC-III scale) and a Magnetic Resonance (MR) examination including conventional sequences to assess brain structural abnormalities and high resolution 3D images for voxel based morphometry (VBM) analysis. To investigate to what extent the group influenced gray matter volumes, both univariate and multivariate generalized linear model analysis of variance were used, and the varimax factor analysis was used to explore variable correlations and clusters among subjects. Results showed that BIF children, compared to controls have increased regional gray matter volume in bilateral sensori-motor and right posterior temporal cortices and decreased gray matter volume in right parahippocampal gyrus. Gray matter volumes were highly correlated with IQ indices. Our is a case study of a group of BIF children showing that BIF is associated with abnormal cortical development in brain areas that have a pivotal role in motor, learning and behavioral processes. Our findings, although allowing for little generalization to general population, contributes to the very limited knowledge in this field. Future longitudinal MR studies will be useful in verifying whether cortical features can be modified over time even in association with rehabilitative intervention.